2003
DOI: 10.1242/jeb.00419
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock response and temperature resistance in the deep-sea vent shrimp Rimicaris exoculata

Abstract: The shrimp Rimicaris exoculata swarms around hydrothermal black smoker chimneys at most vent sites along the Mid-Atlantic Ridge. This species maintains close proximity to the hydrothermal fluid, where temperatures can reach 350°C and steep thermal and chemical gradients are expected. We performed in vivo experiments in pressurized aquaria to determine the upper thermal limit [critical thermal maximum (CTmax)] of R. exoculata and to investigate some characteristics of the shrimp stress response to heat exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 31 publications
1
107
0
Order By: Relevance
“…Th us, sublethal eff ects at moderate temperatures may also be important. For example, a deep-sea vent shrimp ( Rimicaris exoculata ) produces an inducible heat-shock protein (in the hsp70 family) at < 25 ° C 29 . A recent study has also shown that increasing temperature above 25 ° C induces metabolic depression in a vent mussel ( Bathymodiolus azoricus ) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Th us, sublethal eff ects at moderate temperatures may also be important. For example, a deep-sea vent shrimp ( Rimicaris exoculata ) produces an inducible heat-shock protein (in the hsp70 family) at < 25 ° C 29 . A recent study has also shown that increasing temperature above 25 ° C induces metabolic depression in a vent mussel ( Bathymodiolus azoricus ) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In the IPOCAMP, incubations with isotopic tracers were carried out in flasks filled till to the top with seawater (SW), whose volume (50 or 250 ml) was chosen according to the treatment duration and number of shrimps to ensure shrimp survival in good physiological condition at the end of the experiment (Shillito et al, 2001;Ravaux et al, 2003). Incorporation of 13 C-and 14 C-bicarbonate by the chemoautotrophic bacteria was tested with different chemical energy sources.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon uptake by a vent shrimp and its bacteria J Ponsard et al bacteria in good physiological condition (Ravaux et al, 2003). Accordingly, Zbinden et al (2008) observed o30% degraded epibionts in re-pressurised shrimps.…”
Section: Carbon Fixation By Bacterial Chemosynthesismentioning
confidence: 99%
“…A hermit crab was selected at random and its shell secured to a clear plastic Petri dish using dental wax, ensuring that the opening of the shell faced upwards so that the hermit crab could be viewed from above at all times unless it was completely withdrawn inside the shell. This was then placed inside the IPOCAMP ™ upon a tripod platform, which raised the position of the hermit crab inside the pressure chamber, allowing it to be viewed more clearly using en endoscope (see Ravaux et al, 2003). The IPOCAMP ™ was then set running at atmospheric pressure for 30 min to allow the hermit crab to acclimatize and recover from handling stress.…”
Section: Behavioural Measurementsmentioning
confidence: 99%